CONTEMPLATING RELIGIOUS WORK ETHICS IN 'THE PURSUIT OF HAPPYNESS' AND 'DOA YANG MENGANCAM' - Dendri Endrian Ramadhan; Danial Hidayatullah (Leksema: Jurnal Bahasa dan Sastra, 2023)
The two films The Pursuit of Happyness (2006) and Doa yang Mengancam (2008) as the representations of Protestant and Muslim communities both demonstrate significant implications toward the dynamics of work ethics. The problem addressed by this comparison of two cinematic works is the influences of two different religious values on personal work ethics. The foundation of comparative literature paradigm is the idea that by studying literary works from various cultural and linguistic contexts, we can better understand how historical and cultural situations form human experiences--in this case, religious work ethics--occur. The aim of this research is to compare the representation of work ethics within the two main characters in the films as influenced by their respective religious values. The theory used for solving the case is Stuart Hall's (1997) representation theory by using the constructivism paradigm (symbolic, image, discursive, and myth function) with qualitative research method. The findings show that Chris, as a Protestant, has higher work ethics than Madrim, a young Muslim, according to Max Weber's Protestant Ethic principles. However, this situation has an impact on the Protestant’s attitude which is more materialistic than that of the Muslim which shows an equality between worldly wealth and good deeds in the afterlife.